Understanding the Victorians politics, culture and society in nineteenth-century Britain - Steinbach, Susie L. (Routledge, Taylor & Francis Group, 2017)
"Understanding the Victorians paints a vivid portrait of this era of dramatic change, combining broad survey with close analysis and introducing students to the critical debates taking place among historians today. Encompassing all of Great Britain and Ireland over the whole of the Victorian period, it gives prominence to social and cultural topics alongside politics and economics and emphasises class, gender, and racial and imperial positioning as constitutive of human relations. This second edition is fully updated throughout, containing a new chapter on leisure in the Victorian period, the most recent historiographical research in Victorian Studies, and enhanced coverage of imperialism and working-class life. Beginning with the Queen Caroline Affair in 1820 and coming up to the start of World War I in 1914, Susie L. Steinbach uses thematic chapters to discuss and evaluate topics such as politics, imperialism, the economy, class, gender, the monarchy, arts and entertainment, religion, sexuality, religion, and science. There are also three chapters on space, consumption, and the law, topics rarely covered at this introductory level. With a clear introduction outlining the key themes of the period, a detailed timeline, and suggestions for further reading and relevant internet resources, this is the ideal companion for all students of the nineteenth century" --Provided by publisher.